Between Past and Future - 1/16
Recording of an event which is part of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference held at CEU in March 1999. The CEU Bookshop hosted a special celebration launch for “The Revolutions of 1989”, a volume edited by Vladimir Tismăneanu with the contributions of Adam Michnik, Timothy Garton Ash, Jacques Rupnik, Katherine Verdery and Jeffrey Isaac. Introductory remarks about the book and its editor are delivered by Academic Pro-Rector and CEU Professor Sorin Antohi. The beginning of the forth panel entitled “Vulnerabilities of the New Democracies” starts with its chairman John Lampe (Professor at the University of Maryland) reading a letter from Ivan Vejvoda (Director of the Fund for an Open Society Yugoslavia) who could not be present at the conference. Speakers in the panel are Katherine Verdery (Professor at the University of Michigan), Gail Kligman (University of California Los Angeles), Kazimierz Poznanski (Professor at the University of Washington), István Rév (Professor at CEU and Director of OSA Archivum) and Miklós Haraszti (Hungarian Writer, Journalist and Professor). Prof. Katherine Verdery is the first speaker of the fourth panel and she is followed shortly by Prof. Gail Kligman.